Analgesic and antiinflammatory activities of the capilliposide derived from Lysimachia capillipes Hemsl., a traditional Chinese medicinal herb - Wu, Zhipan; Han, Haote; Xu, Mengting; Shen, Yuhang; Gao, Chengcheng; Yuan, Huahua; Li, Shouxin; Tian, Jingkui; Ye, He (Archives of Biological Sciences, 2020)
Paper description: The Lysimachia capillipes Hemsl capilliposide (LCc) is the main bioactive component of this Chinese medicinal plant. Hot-plate, body torsion and paw swelling tests, together with changes in MDA, PGE2, TNF-α, COX-1 and COX-2 levels in paw tissues determined by ELISA served to estimate the analgesic and anti-inflammatory effects of LCc in female IRC mice. The presented results describe analgesic and anti-inflammatory effects of LCc and lay the foundations for further investigations of its bioactivity. Abstract: Pain and inflammation are associated with the pathophysiology of different clinical conditions. The Lysimachia capillipes Hemsl. capilliposide (LCc) is the main bioactive component of this Chinese medicinal herb, which is widely used as a remedy for the treatment of colds and arthritis. This study investigated the analgesic and antiinflammatory activities of LCc in an animal model. LCc had no significant influence on the spleen, lung, liver and stomach coefficients in mice. Pharmacological studies showed that LCc at all doses (40, 60 and 90 mg/kg) increased the latency period of paw licking induced by thermal stimulation, and at the dose of 40 mg/kg it significantly suppressed abdominal writhing episodes of mice induced by intraperitoneal (i.p.) injection of acetic acid. LCc also had antiinflammatory effect on inflammation models. Doses of 60 and 90 mg/kg suppressed paw edema induced by subcutaneous (s.c.) injection of carrageenan. Mechanistic studies revealed that the antiinflammatory effect of LCc was associated with inhibition of the production of malondialdehyde (MDA), prostaglandin E2 (PGE2), tumor necrosis factor (TNF-α), cyclooxygenase-1 (COX-1) and cyclooxygenase-2 (COX-2) in paw tissue of carrageenan-injected mice. These results show that LCc has analgesic and antiinflammatory effects in mice.